A Survey of Sulfur-bearing Molecular Lines toward the Dense Cores in 11 Massive Protoclusters - Mengyao Tang; Sheng-Li Qin; Tie Liu; Luis A. Zapata; Xunchuan Liu; Yaping Peng; Fengwei Xu; Chao Zhang; Ken’ichi Tatematsu (The Astrophysical Journal Supplement Series)
Sulfur-bearing molecules are commonly detected in dense cores within star-forming regions, but the total sulfur budget is significantly lower when compared to the interstellar medium value. The properties of sulfur-bearing molecules are not well understood due to the absence of large sample studies with uniform observational configurations. To deepen our understanding of this subject, we conducted a study using Atacama Large Millimeter/submillimeter Array 870 μ m observations of 11 massive protoclusters. By checking the spectra of 248 dense cores in 11 massive protoclusters, a total of 10 sulfur-bearing species (CS, SO, H _2 CS, NS, SO _2 , ^33 SO, ^34 SO _2 , ^33 SO _2 , SO ^18 O, and OC ^34 S) were identified. The parameters including systemic velocities, line widths, gas temperatures, column densities, and abundances were derived. Our results indicate that SO appears to be more easily detected in a wider range of physical environments than H _2 CS, despite these two species showing similarities in gas distributions and abundances. Molecules ^34 SO _2 and H _2 CS are good tracers of the temperature of sulfur-bearing species, in which H _2 CS traces the outer warm envelope and ^34 SO _2 is associated with high-temperature central regions. High-mass star-forming feedback (outflow and other nonthermal motions) significantly elevates the sulfur-bearing molecular abundances and detection rates specifically for SO _2 and SO. A positive correlation between the SO _2 abundance increasing factor ( F ) and temperatures suggests that SO _2 could serve as a sulfur reservoir on the grain mantles of dense cores and then can be desorbed from dust to gas phase as the temperature rises. This work shows the importance of a large and unbiased survey to understand the sulfur depletion in dense cores.